Synthesis and quality control of [18F]T807 for tau PET imaging. (17th July 2016) - Holt, Daniel P.; Ravert, Hayden T.; Dannals, Robert F.
Abstract : The detailed synthesis and quality control of [ 18 F]T807, radiotracer for tau protein aggregate imaging, are described. The radiotracer synthesis was accomplished in an average of 48 min with an average specific activity at end‐of‐synthesis of over 4.4 TBq/µmole (120 Ci/µmole) and an average radiochemical yield of 32%. Compliance with all standard US Pharmacopeia Chapter <823> acceptance tests was observed. Abstract : The detailed synthesis and quality control of [ 18 F]T807, radiotracer for tau protein aggregate imaging, are described. The radiotracer synthesis was accomplished in an average of 48 min with an average specific activity at end‐of‐synthesis of over 4.4 TBq/μmole (120 Ci/μmole) and an average radiochemical yield of 32%. Compliance with all standard USP Chapter <823> acceptance tests was observed.